ANALYSIS OF POLICY AND ENVIRONMENTAL MANAGEMENT IN THE CITY OF ITAPIPOCA, CEARÁ - Xirlean Xavier Alves, Francisco; Jeferson Sampaio Diogo, Ivan (Journal of Interdisciplinary Debates, 2021)
The Environmental Policy is a set of activities and procedures aimed at the management of the environment and coordinated by the different levels of competence and supranational organizations, of the State and non-governmental companies and organizations, which intend to reach the final goal of protecting the environment. and nature conservation. Brazilian municipalities face a series of problems in relation to environmental management. The objective of this research was to analyze the environmental policy in the municipality of Itapipoca-CE based on its environmental licensing and activities, and inspection actions. A qualitative, descriptive case study was carried out, establishing a relationship between the factors addressed in this work and those of a bibliographic nature. The municipality of Itapipoca has great potential for diverse economic activities. Comparing the data of the records drawn up over the years 2017, 2018 and until July 2019, there is an increase in complaints, inspections and environmental assessments. In addition, different Environmental Education strategies were observed in the application of projects and actions at the municipal level. The assessment of the management and environmental policy of the municipality of Itapipoca-CE showed the clear process of decentralization, where municipalities are organizing themselves and taking action in relation to their environmental issues, where licensing and inspection activities are increasingly being carried out.